Design of Mine Distribution System at Nickel Mining Front of Pt. Cipta Djaya Surya - Mulyadi Mulyadi; Muhammad Chaerul; Natsar Desi; Erniati Bachtiar; A. Yusuf Harun; Ismail Marzuki (Newinera Publisher, 2026)
Nickel mining activities at PT. Cipta Djaya Surya in Molore Village, North Konawe Regency, face a serious problem in the form of stagnant runoff in the mine front area due to the lack of an adequate drainage system and sedimentation pond. This condition not only disrupts smooth mining operations but also has environmental impacts, such as reddish discoloration of coastal waters and potential siltation. This study aims to analyze surface runoff discharge, design open channel dimensions, and design settling ponds appropriate to the hydrological and topographical conditions of the study site. The methods used include collecting rainfall data for the past 10 years from the Meteorology, Climatology, and Geophysics Agency (BMKG), hydrological analysis using the rational method, hydraulic calculations using the Manning equation, and planning channel and settling pond dimensions based on runoff discharge. The results indicate that the maximum runoff discharge in the study area can be managed by designing a trapezoidal open channel with dimensions appropriate to the flow capacity, while the designed settling pond can accommodate the runoff volume without overflowing. The implementation of a planned drainage system is expected to maintain smooth mining operations, minimize the risk of landslides, and mitigate the impact of coastal environmental pollution. Therefore, this research supports the implementation of Good Mining Practice (GMP) principles and can be used as a reference in sustainable mine drainage planning.